Amino acid production exceeds plant nitrogen demand in Siberian tundra. (16th February 2018) - Wild, Birgit; Alves, Ricardo J Eloy; Bárta, Jiři; Čapek, Petr; Gentsch, Norman; Guggenberger, Georg; Hugelius, Gustaf; Knoltsch, Anna; Kuhry, Peter; Lashchinskiy, Nikolay; Mikutta, Robert; Palmtag, Juri; et al.
Abstract: Arctic plant productivity is often limited by low soil N availability. This has been attributed to slow breakdown of N-containing polymers in litter and soil organic matter (SOM) into smaller, available units, and to shallow plant rooting constrained by permafrost and high soil moisture. Using 15 N pool dilution assays, we here quantified gross amino acid and ammonium production rates in 97 active layer samples from four sites across the Siberian Arctic. We found that amino acid production in organic layers alone exceeded literature-based estimates of maximum plant N uptake 17-fold and therefore reject the hypothesis that arctic plant N limitation results from slow SOM breakdown. High microbial N use efficiency in organic layers rather suggests strong competition of microorganisms and plants in the dominant rooting zone. Deeper horizons showed lower amino acid production rates per volume, but also lower microbial N use efficiency. Permafrost thaw together with soil drainage might facilitate deeper plant rooting and uptake of previously inaccessible subsoil N, and thereby promote plant productivity in arctic ecosystems. We conclude that changes in microbial decomposer activity, microbial N utilization and plant root density with soil depth interactively control N availability for plants in the Arctic.